Islamic Ethical Perspective of Environmental Abuse in Lagos State Nigeria - Musthapa Adebayo Bello (IAIN Ponorogo, 2022)
The mega city of Lagos is increasingly bugged down by environmental challenges threatening the developmental agenda of successive regimes since the beginning of the 4th republic. With an estimated population of 21 million people, the environmental landscape is replete with the shattering of the basic elements of nature- land, air and water- which sustain life as a result of human indiscretion in the treatment of the environment. Such abuses constitute daily challenges being addressed by various environmental agencies in the State. Many of such governmental efforts bordering on the management of the physical consequences of environmental abuse have really not addressed the unethical human conducts which more often than not precipitate such avoidable environmental convulsions threatening sustainable development. Contrastingly, religious establishment also on their own focuses on moral protection of the environment thereby revealing a glaringly dichotomy between the approaches. This widening gap is the focus of this paper. Using exploratory and qualitative methods, this study interrogates the Islamic integrated approach as it relates with the roles of Islamic advocacy platform (Minbar) and tool (Khutbah) in the sustenance of the ecological balance ingrained into nature ab initio by Allah.